Building Clinical Nutrition Capacity in sub-Saharan Africa: Experiences of Developing a Post Graduate Diploma in Dietetics in Malawi. - Nkomani, Sanele. (Tufts University. Tisch Library., 2018)
This poster describes the 20 month long postgraduate diploma program at Lilongwe University of Agriculture and Natural Resources.; Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy